Pola Interaksi Orang Tua dalam Membentuk Karakter Nilai Spiritual Anak Usia Dini pada Masa Pandemi Covid 19 - Habibah, Nur Faiz (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
Early childhood development starts from physical and psychological which requires guidance and direction from parents. The formation of a child's spiritual character becomes the provision of children's knowledge after he passes through the early childhood years. This study aims to explain the formation of the character of early childhood spiritually with the interaction between parents and children. This study uses a qualitative approach, with the location of Krajan Hamlet, Kebaman Village, Srono District, Banyuwangi Regency. Data were collected by observation, interview and analysis methods. Testing the validity of the data is measured using source triangulation techniques, methods, extension of observation time, checking. Data reduction, data display and conclusions in analyzing. Parental interactions have a positive impact on children. More intensity of time with children during a pandemic gives better results, because parents are able to be more intensive in providing guidance to children. The results of the interaction of parents in shaping the character of children are better in getting used to religious activities from an early age, during the pandemic.